Perilaku Konsumen Asuransi terhadap Keputusan Pembelian - Ayu Lestari; Nuri Aslami (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2022)
The purpose of this article is to determine the behavior of insurance consumers towards purchasing decisions on insurance products. Both in terms of types of consumer behavior, decision-making processes, the benefits of studying consumer behavior, consumer perceptions .What products are currently needed by prospective customers. In Insurance, it is very important to know about the marketing mix, which refers to a unique blend of product, distribution, promotion and pricing strategies designed to generate mutually beneficial exchanges.Satisfied with the target market. The marketing mix consists of 4Ps, namely, product, price, place. Keywords: Consumer behavior, purchasing decisions, insurance